Effect of Group Learning with Primary Education Students - Eliza Avdiu (ÜNİVERSİTEPARK Limited, 2019)
The purpose of this research is to examine group learning and its impact on achieving knowledge for primary school students. In this quasi-experimental study, data were collected from 221 students, with 111 students in an experimental group (who were influenced to learn through cooperative learning strategies) and 110 students in a control group (who learned under normal conditions). The total number of teachers was 50 from both groups. SPSS statistical package was used in this research with the following parameters: median, standard deviation, t-test, and correlation. Students achievement tests were conducted in both groups both prior to and following the experimental process in order to see the effects on students' achievements. The results of the analysis have shown that cooperative learning strategies have a significant effect on student achievement in learning. This has been proven through differences seen in the final success of students in the control and experimental groups, which showed significant statistical value in favor of the experimental group. This research also provides information on the effects of the implementation of group work in teaching, which resulted in higher student achievement based on engagement, and the educational and professional background of teachers as a potential factor in attracting students to active cooperative learning. Based on these results, implications point to the insufficient dedication of teachers during the group learning process.